2022
DOI: 10.1088/1361-6668/ac68a6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of BaSnO3 and BaZrO3 nanoinclusions on the critical current and local structure of HTS coated conductors

Abstract: We studied the effect of artificial pinning centers in the form of nanoinclusions of stannate BaSnO3 (BSO) and zirconate BaZrO3 (BZO) barium on the critical current of high-temperature superconducting tapes of the second generation (2G) based on YBa2Cu3O7−δ films (YBCO). It has been found that the introduction of BaZrO3 nanoinclusions increases the critical current at 77 K for the magnetic field direction parallel and normal to the tape surface, while the introduction of BaSnO3 nanoinclusions decreases the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…В частности, в работах [12,13] было показано, что наночастицы BaZrO 3 имеют высокие перспективы как кандидаты в инертные центры пиннинга. Исследования по созданию искусственных центров пиннинга на основе нанодобавок проводились для ВТСП-пленок, полученных различными методами: импульсного лазерного напыления [14,15,16], металлоорганического осаждения жидких прекурсоров [17,18], осаждения металлорганических соединений из газообразной фазы [10,11,[19][20][21][22][23]. Наряду с монодобавками, рассматривался способ создания структур с комбинацией точечных и колончатых дефектов [24].…”
Section: Introductionunclassified
“…В частности, в работах [12,13] было показано, что наночастицы BaZrO 3 имеют высокие перспективы как кандидаты в инертные центры пиннинга. Исследования по созданию искусственных центров пиннинга на основе нанодобавок проводились для ВТСП-пленок, полученных различными методами: импульсного лазерного напыления [14,15,16], металлоорганического осаждения жидких прекурсоров [17,18], осаждения металлорганических соединений из газообразной фазы [10,11,[19][20][21][22][23]. Наряду с монодобавками, рассматривался способ создания структур с комбинацией точечных и колончатых дефектов [24].…”
Section: Introductionunclassified
“…In particular, in [12,13] it was shown that nanoparticles of BaZrO 3 are very promising as candidates for inert centers of pinning. Investigations focused on the creation of artificial centers of pinning based on nanoadditives were carried out for HTS tapes produced by different methods: pulsed laser deposition [14][15][16], liquid delivery metal-organic precursors for the chemical vapor deposition [17,18], metal-organic compounds for the chemical vapor deposition [10,11,[19][20][21][22][23]. Along with monoadditives, a method of structure creation with a combination of point and columnar defects was considered [24].…”
Section: Introductionmentioning
confidence: 99%